Pitcairnia yocupitziae (Bromeliaceae; Pitcairnioideae), a remarkable new species from Guerrero, Mexico - Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa (Instituto de Ecología, A.C., 2010)
Pitcairnia yocupitziae Espejo & López-Ferrarri, sp. nov. (Bromeliaceae), known only from the state of Guerrero, Mexico, is described and illustrated. The new species is compared with P. roseana L. B. Sm., from which it differs by its inflorescence and floral bracts. An identification key for the species of Pitcairnia present in Guerrero is also included.